Effect of crop-establishment and tillage practices on yield and economics of irrigated rice (Oryza sativa) - wheat (Triticum aestivum) system - Sharma, S K; Tomar, R K; Gangawar, K S (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was conducted during 1991-92 and 1992-93 to evaluate the crop-establishment and tillage practices forirrigated rice (Oryza sativa L.)-wheat (Triticum aestivum L. emend. Fiori & Paol.) system in decreasing labour or energyrequirement of the system. Grain yield of rice and wheat was not affected significantly due to different methods of rice cropestablishment and tillage practice followed in wheat. However, higher total productivity of 9.30 tonnes/ha was recorded underdirect-seeded, puddled condition, followed by transplanting (9.10 tonnes/ha) and direct-seeded, dry condition (8.99tonnes/ha). Owing to substantial saving of labour under direct-seeded, puddled condition higher net return of Rs 147 41/hawas obtained compared with Rs 13 498/ha under direct-seeded, dry condition and Rs 12981 /ha under transplanting. Differenttillage practices adopted for wheat cultivation gave similar yields and indicated that reduced tillage (with 1 harrow + 1cultivator) was more remunerative than optimum tillage (wilh. 2 harrows + 2 cultivators) owing to substantial saving of Rs406/ha under the reduced tillage.